Long-Term Observations of the Thermospheric 6 h Oscillation Revealed by an Incoherent Scatter Radar over Arecibo - Yun Gong; Yaxuan Ding; Xinkun Chen; Shaodong Zhang; Qihou Zhou; Zheng Ma; Jiahui Luo (Remote Sensing, 2023)
We present an analysis of 6 h oscillations in the thermosphere ranging from 150 km to 400 km. The analysis applies 134 days of data from an incoherent scatter radar located at Arecibo Observatory (18.3°N, 66.7°W) from 1984 to 2015. To our knowledge, the climatological and seasonal characteristics of the 6 h oscillations in the thermosphere were investigated for the first time over Arecibo. The climatological mean amplitude of the 6 h oscillation in the thermosphere is about 11 m/s, and it increases slowly with altitude above 225 km. The climatological mean amplitude of the 6 h oscillation is comparable with semidiurnal and terdiurnal tides at Arecibo above 250 km. The climatological mean phase exhibits limited vertical variation. The 6 h oscillation is the most prominent in autumn, with amplitudes reaching around 20 m/s compared to approximately 10 m/s in other seasons. The phase structure in all seasons exhibits weak vertical variations. The responses of the thermospheric 6 h oscillation to solar and geomagnetic activities are also analyzed in this study. Our results indicate that at low latitude, solar activities have a small impact on the variation in the thermospheric 6 h oscillation, while it appears that the amplitude of the 6 h oscillation increases with increasing geomagnetic activity. Above 250 km, the amplitude of the 6 h oscillation reaches ~20 m/s during strong geomagnetic activity, which is almost twice of that occurring during weak geomagnetic activity.